The Process of Developing a Sleep Health Improvement Plan: a Lab-Based Model of Self-Help Behavior. - Irish, Leah A.; Veronda, Allison C.; van Lamsweerde, Amanda E.; Mead, Michael P.; Wonderlich, Stephen A. (International Journal of Behavioral Medicine, 2021)
Background: Although self-help strategies to improve sleep are widely accessible, little is known about the ways in which individuals interact with these resources and the extent to which people are successful at improving their own sleep based on sleep health recommendations. The present study developed a lab-based model of self-help behavior by observing the development of sleep health improvement plans (SHIPs) and examining factors that may influence SHIP development. Method: Sixty healthy, young adults were identified as poor sleepers during one week of actigraphy baseline and recruited to develop and implement a SHIP. Participants viewed a list of sleep health recommendations through an eye tracker and provided information on their current sleep health habits. Each participant implemented their SHIP for 1 week during which sleep was assessed with actigraphy. Results: Current sleep health habits, but not patterns of visual attention, predicted SHIP goal selection. Sleep duration increased significantly during the week of SHIP implementation. Conclusions: Findings indicate that the SHIP protocol is an effective strategy for observing self-help behavior and examining factors that influence goal selection. The increase in sleep duration suggests that individuals may be successful at extending their own sleep, though causal mechanisms have not yet been established. This study presents a lab-based protocol for studying self-help sleep improvement behavior and takes an initial step toward gaining knowledge required to improve sleep health recommendations.